STUDI AKUMULASI LOGAM BERAT MERKURI (Hg) OLEH TANAMAN TREMBESI (Samanea saman) - Dian Kilikily; Abraham Mariwy; Sunarti Sunarti (Science Map Journal, 2020)
One effort to mitigate the pollution of weight Metal mercury (Hg) in soil with the process of fitoremediation or plant use that is categorized as a hyperaccumulator plant.This research aims to determine the magnitude of the accumulation of weight metal mercury (Hg) by the Trembesi plant (Samanea Saman) based on the value of Biocentration factor (BCF) and the translocation factor (TF) with variation of time of contact between plants with land tainted seven days and fourteen days. Research conducted in integrated research and testing laboratory of Gadjah Mada University Yogyakarta (LPPT-UGM) with Mercury instrument Analyzer. The results of the study showed that the highest mercury uptake (Hg) was found at a seven-day remediation time with a concentration of absorption at roots of 5.16 ppm and at a leaf of 1.90 ppm. While the result of the calculation shows that the value of the biocentralization factor (BCF) is 5.27 and the value of translocation (TF) 0.36 so that Trembesi plant (Samanea Saman) can be categorized as one of the accumulator plants against contaminated weight metal mercury (Hg) because it has a value of BCF > 1 with fitostabilisation mechanism